PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH - Yuswianti, N Susi; Herlina, N Hani; Rohman, Ahmad Abdur (Jurnal Penelitian Pendidikan Islam, 2016)
The purpose of this study was to determine the improvement of student learning achievement on Fiqh subjects by using audio visual media. This study yields the following conclusions: 1) the ability of teachers to develop RPP using audio visual media in the subjects of jurisprudence in the subject of Hajj is increasing. This can be seen from the percentage of observations every cycle that continues to increase. Cycle I was 77.50%, cycle II was 83.50%, cycle III was 87%. 2) The implementation of learning using audio visual media in the subjects of jurisprudence the subject of Hajj is also increasing. This is evidenced by the percentage of results of observations of implementation in each cycle there is an increase. Cycle I 71.50%, cycle II 84.65%, cycle III 85.25%; 3) Student learning achievement also increases. It is proven that each aspect increases in each cycle. Cycle I spiritual aspects 72%, social aspects 73.50%, aspects of knowledge 80.31%, aspects of skills 80.50%. Cycle II spiritual aspects 75.36%, social aspects 78.49%, aspects of knowledge 83.59%, aspects of skills 82%. Cycle III on spiritual aspects 78.24%, social aspects 81.60%, aspects of knowledge 86.25%, and aspects of skills 84.50%.